GRAPH-ANALYTICAL METHOD FOR DETERMINATION OF CAVITATION AREAS IN OIL PIPELINES IN STEADY REGIME - Vali Nurullayev; Gafar Ismayilov (Proceedings on Engineering Sciences)
The article provides an overview of free-flow fields and lists the conditions and consequences of their formation, currently known as a hydraulic phenomenon. It is noted that the study and determination of free flow areas is of particular importance for the safe and efficient operation of the oil pipeline system. Although the consumption of oil in the free-flow areas of the pipeline is the same in the steady-state operation, the flow rates are different. Because the velocity in the pressure zone is lower than the velocity in the free flow zone, according to the law of continuity, the movement of the liquid in the latter zones does not occur along the entire cross-section of the pipe. For this, the authors have developed a grapho-analytical method for determining free flow areas in oil pipelines in a fixed mode. The possibility of determining the location and volume of free flow zones in oil pipelines in the determined movement modes by the proposed grapho-analytical method was shown, and the results of the test of the method in a real oil pipeline were satisfactory.